An Observational Cohort Study on Delayed-Onset Infections after Mandibular Third-Molar Extractions - Brunello, Giulia; De Biagi, Marleen; Crepaldi, Giulia; Rodrigues, Fernanda Izaura [UNESP]; Sivolella, Stefano (Hindawi, 2017)
Objectives. The purpose of the present study was to investigate the occurrence and clinical features of delayed-onset infections after mandibular third-molar extractions. Method and Materials. An observational cohort study was conducted on 179 patients undergoing mandibular third-molar extraction between January 2013 and December 2015, for a total of 217 extractions. Data were recorded at the time of extraction (T0), on suture removal seven days later (T1), and 30 days after the extraction, when patients were contacted and asked about their healing process (T2). The statistical analysis was performed with nonparametric tests. A p value lower than 0.05 was considered statistically significant. Results. Eight delayed-onset infections were recorded, amounting to 3.7% of all extractions. The median time elapsing from the extraction to the delayed-onset infection was 35 days (IQR 28-40; min 24-max 49). Younger age and longer surgical procedures seemed to be more often associated with this complication. Conclusion. Delayed-onset infections after third-molar extractions are relatively rare postoperative complications characterized by a swelling, usually with a purulent discharge. Patients should be informed of this possibility, which might develop even several weeks after the extraction.